2012
DOI: 10.1007/s10853-012-6451-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotube/silver nanoparticles used for thermal transportation

Abstract: A green method was applied to prepare composites of multi-walled carbon nanotubes (MWNTs) decorated with silver nanoparticles (Ag-NPs). MWNTs were functionalized using ball milling technology in the presence of ammonium bicarbonate, and the traditional method of silver mirror was used to decorate MWNTs to obtain Ag/MWNT composite. The obtained Ag/MWNT composites were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transmission infrared spectroscopy, and Brunauer-Emmet-Tell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 57 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…The peak at 1 718 cm −1 suggests the presence of stretching CO vibrations arising from carboxylic acids . The peaks at ≈1 660 cm −1 is usually attributed to the carbonyl groups and CC . Comparing to that of MWCNTs, the FT‐IR peaks of PAA‐MWCNTs at ≈1 660 cm −1 is significantly improved, which can be due to the COOH groups in PAA on the surface of PAA‐MWCNTs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The peak at 1 718 cm −1 suggests the presence of stretching CO vibrations arising from carboxylic acids . The peaks at ≈1 660 cm −1 is usually attributed to the carbonyl groups and CC . Comparing to that of MWCNTs, the FT‐IR peaks of PAA‐MWCNTs at ≈1 660 cm −1 is significantly improved, which can be due to the COOH groups in PAA on the surface of PAA‐MWCNTs.…”
Section: Resultsmentioning
confidence: 98%
“…Smitha et al reported that PAA present typical FT‐IR peaks at ≈3 410, ≈1 720, and ≈1 450 cm −1 , which can be assigned to carbonyl groups, and, respectively. The broad peak at 1 612 cm −1 can be due to the vibrations of carbonyl groups or to skeletal CC aromatic vibrations of MWCNTs . The peak at 1 718 cm −1 suggests the presence of stretching CO vibrations arising from carboxylic acids .…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al studied the synergistic effects of Ag/MWNT composites on the thermal conductivity of the water-based nanofluids [86]. The measurement results showed that the thermal conductivity of the water-based nanofluids containing Ag/MWNT composites was higher than that of those containing pristine or functionalized MWNTs (Figure 12).…”
Section: The Synergistic Effect Of 1d Nanomaterials and 0dmentioning
confidence: 99%
“…So in the work reported here, we hoped to prepare CNT‐Ag for further application in spinning. To date, a number of authors have reported various methods for the preparation of CNT‐Ag, such as chemical reduction, γ‐irradiation‐induced reduction, high‐temperature reduction, vapor‐phase deposition, etc. However, all of these routes show some disadvantages, such as reducing agent remaining as impurity, expensive equipment cost, high energy consumption and complicated production process.…”
Section: Introductionmentioning
confidence: 99%